2021
DOI: 10.1148/radiol.2020203453
|View full text |Cite
|
Sign up to set email alerts
|

Variations in CT Utilization, Protocols, and Radiation Doses in COVID-19 Pneumonia: Results from 28 Countries in the IAEA Study

Abstract: Background There is lack of guidance on specific CT protocols for imaging patients with coronavirus disease 2019 (COVID-19) pneumonia. Purpose To assess international variations in CT utilization, protocols, and radiation doses in patients with COVID-19 pneumonia. Materials and Methods In this retrospective data collection study, the International Atomic Energy Agency (IAEA) coordinated a survey between May and July 2020 regarding CT utilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
91
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 17 publications
6
91
0
Order By: Relevance
“…According to a large multicentre study by the IAEA, most of the centres involved did not use CT for the first diagnosis, but possibly as a tool for assessing the severity of lung involvement. The use of CT at the patient’s entry point would be justified in a situation of high prevalence of suspicious clinical presentations and a lack of means to timely obtain RT-PCR swabs results [ 5 ]. This tendency was still apparent during phase 2, when the amount of chest CT scans failed to set back to the pre-COVID-19 levels as shown by the statistically significant differences observed in the respective frequency distribution between phase 0 and phase 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a large multicentre study by the IAEA, most of the centres involved did not use CT for the first diagnosis, but possibly as a tool for assessing the severity of lung involvement. The use of CT at the patient’s entry point would be justified in a situation of high prevalence of suspicious clinical presentations and a lack of means to timely obtain RT-PCR swabs results [ 5 ]. This tendency was still apparent during phase 2, when the amount of chest CT scans failed to set back to the pre-COVID-19 levels as shown by the statistically significant differences observed in the respective frequency distribution between phase 0 and phase 2.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 70% of the Italian imaging providers have focused their activity on emergency studies and procedures [ 4 ]. Conversely, the rostering of the ERD reflected this, to accommodate the increasing demand for chest CTs, which have been widely used as a crucial diagnostic and prognostic tool in patients with both suspected and confirmed COVID-19 [ 5 ]. For instance, medical and technical staff presence in the ERD was doubled at all times.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Radiology , the article by Homayounieh et al ( 1 ) provides valuable descriptive data to begin filling these knowledge gaps by presenting variations in CT utilization, protocols, and dose in COVID-19 patients across 34 countries. The authors surveyed 62 healthcare sites from these countries across four continents covering Africa, Asia, Europe, and Latin America between May and July 2020, in a coordinated effort by the International Atomic Energy Agency.…”
mentioning
confidence: 99%
“…CT acquisition with either low or standard dose is controversial, as well. International Atomic Energy Agency (IAEA) coordinated a multicenter study about CT use in 28 countries in COVID-19 and found that only 20% of the centers used reduced-dose (lower than routine protocol) (18). Some authors had reliable results using low-dose CT (19,20).…”
Section: Discussionmentioning
confidence: 99%